The Supply and Demand Analysis of a Spicy Smashed Fried Chicken Business Using Linear Functions in Mathematics Learning - Wati, Erma; Hakim, Abdur Rahman; Rosadi, Farah Fadhilah; Jasca, Jihan Marlinita; Kafrina; Granita (Mathematics Research and Education Journal, 2026)
This study aims to analyze the relationship between demand and supply in a Spicy Smashed Fried Chicken business around UIN Suska Riau and its application in mathematics learning. The research used a descriptive quantitative approach with a case-study design. Primary data were collected in December 2024 on Jl. Buluh Cina, Pekanbaru, through purposive sampling involving one business owner and six observations of daily transactions at different price levels. Data were analyzed using simple linear regression under the assumption of ceteris paribus. The results indicate that an increase of Rp1,000 in price decreases demand by approximately 5 portions per day and increases supply by approximately 5 portions per day. The market equilibrium occurs at a price of Rp12,500 with an equilibrium quantity of around 37–38 portions per day. These findings provide insights for culinary MSMEs in determining pricing strategies based on market conditions, especially among students who are sensitive to price changes. In addition, the resulting linear models can be applied in Realistic Mathematics Education (RME) to help students understand mathematical modeling through real-world contexts